2002
DOI: 10.1063/1.1454226
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of electron cyclotron resonance plasma deposited hydrogenated amorphous carbon and carbon nitride films

Abstract: Hydrogenated amorphous carbon and carbon nitride films (a-C1−xNx:H) have been synthesized from methane, acetylene, or acetylene–nitrogen precursor gases using a high density electron cyclotron resonance plasma. The deposition and etching rates, along with the film stoichiometry, density, Raman signature of the sp2 phase, and optical and transport properties, have been studied as a function of plasma parameters (microwave power and negative bias of the substrate). While low-density H-rich carbon films have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…5 An important electronic property of such carbon based materials, which includes diamond, carbon nanotubes (CNT) and CNT-composites, is their ready ability to emit electrons into vacuum which make them suitable for applications in field emission display technology. 2,7,8 Diamond-like carbon (DLC) thin films are well known for their exceptional mechanical properties [9][10][11][12][13][14] and recently, we have explored the mechanical, optical and electrical properties of DLC and modified DLC thin films. [15][16][17][18][19] DLC thin films are known to emit electrons 20,21 , however, compared with diamond and CNTs, their threshold field (E T ) tends to be higher and emission current (I E ) is lower.…”
Section: Introductionmentioning
confidence: 99%
“…5 An important electronic property of such carbon based materials, which includes diamond, carbon nanotubes (CNT) and CNT-composites, is their ready ability to emit electrons into vacuum which make them suitable for applications in field emission display technology. 2,7,8 Diamond-like carbon (DLC) thin films are well known for their exceptional mechanical properties [9][10][11][12][13][14] and recently, we have explored the mechanical, optical and electrical properties of DLC and modified DLC thin films. [15][16][17][18][19] DLC thin films are known to emit electrons 20,21 , however, compared with diamond and CNTs, their threshold field (E T ) tends to be higher and emission current (I E ) is lower.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Godet et al [36] showed that polymeric a-C:H films exhibiting low mass densities (< 2 g/cm 3 ) and high H content (25%-40%) are grown under low RF bias powers using C2H2 as well as CH4 based ECR discharges while Baby et al [37] found a high average Raman base line slope at lower substrate bias potentials which corresponds to a high H content in the films when they deposited a-C:H films using C2H2/Ar based ICP discharge. In our case similar trends with respect to mass density are observed for films (see Fig.2) grown using HiPIMS+DCMS at Eion = -eVfl, whereas in 100% Ar HiPIMS case (where there is no intentional use of H) the film exhibit higher density at this ion energy values.…”
Section: B Film Growthmentioning
confidence: 99%
“…However, Ronning et al 13 have argued that nitrogen introduction increases the states, which changes the activation energy as well as conductivity. On the other hand, Godet et al 4,14 have suggested that nitrogen introduction causes a reduction of concentration of states and this governs the conduction mechanism.…”
mentioning
confidence: 99%
“…Lazar et al 11 have developed a-C:H based metal-insulator-metal (MIM) and metal-insulator-semiconductor (MIS) structures and observed space charge limited conduction in their devices. While various other conduction mechanisms, which includes band tail hopping have also been reported [2][3][4] in films grown at low pressure, it remains important to understand the physics related to the conduction in a-C:H and modified a-C:H films especially those grown at high pressures.…”
mentioning
confidence: 99%
See 1 more Smart Citation